New insights into the history of rice domestication - Kovach, Michael J.; Sweeney, Megan T.; McCouch, Susan R. (Trends in genetics, 2007)
The history of rice domestication has long been a subject of debate. Recently obtained genetic evidence provides new insights into this complex story. Genome-wide studies of variation demonstrate that the two varietal groups in Oryza sativa ( indica and japonica) arose from genetically distinct gene pools within a common wild ancestor, Oryza rufipogon, suggesting multiple domestications of O. sativa. However, the evolutionary history of recently cloned domestication genes adds another layer of complexity to the domestication of rice. Although some alleles exist only within specific subpopulations, as would be expected if the domestications occurred independently, other major domestication alleles are common to all cultivated O. sativa varieties. Our current view of rice domestication supports multiple domestications coupled with limited introgression that transferred key domestication alleles between divergent rice gene pools.